Potensi Debit Banjir Berdasarkan Periode Ulang 5 Tahunan Sub Das Ciojar - Farhan Fauzaan A; Sulwan Permana (Institut Teknologi Garut, 2026)
Flooding is one of the most frequent and destructive natural disasters, impacting human lives and causing economic damage. According to data from the Indonesian National Disaster Management Agency (BNPB), there were 920 flood incidents recorded in West Java between 2014 and 2023. One major flood event occurred in the Cimanuk River, Garut Regency, in 2016, resulting in significant damage to the surrounding areas. The Cimanuk River is part of a watershed that includes several tributaries or sub-watersheds (Sub-DAS) with potential to cause flooding. The Ciojar Sub-watershed, located in Garut Regency, is one such tributary that frequently contributes to flooding. It flows through residential areas, plantations, and rice fields. Most of the land around the Ciojar Sub-watershed is used for agriculture, while some residential areas lie at lower elevations, making them especially vulnerable to flooding.This study adopts a quantitative approach to analyze the frequency and impact of floods in the region. It has two main objectives: to identify the months and years in which rainfall exceeded the five-year flood threshold (Q5), and to predict flood events exceeding Q5 from 2024 to 2027. Flood discharge was calculated using the Synthetic Unit Hydrograph method from the Soil Conservation Service (SCS), while flood predictions were simulated using an Artificial Neural Network (ANN) Backpropagation method with MATLAB software.The analysis of flood discharge based on a five-year return period for 2014 to 2023 yielded the following values: 99.250 m³/s (2014), 10.459 m³/s (2015), 162.367 m³/s (2016), 194.384 m³/s (2017), 149.485 m³/s (2018), 168.318 m³/s (2019), 162.218 m³/s (2020), 8.870 m³/s (2021), 233.587 m³/s (2022), and 124.346 m³/s (2023).The predicted flood discharges for the five-year return period from 2024 to 2027 are: 128.513 m³/s (2024), 93.488 m³/s (2025), 78.318 m³/s (2026), and 172.255 m³/s (2027).